Three-dimensional inversion resolution in detecting stagnant slabs using a dense geomagnetic depth sounding method - Zhang, Yanhui; Yang, Yue (Physics of the earth and planetary interiors, 2022)
Although seismic tomography has revealed the stagnancy of the western Pacific plate beneath northeastern China, dynamic simulation shows that stagnant slabs sink into the lower mantle after a transient stagnation. In this study, numerical simulation was used to determine whether geomagnetic depth sounding (GDS) can detect broken plates in the uppermost lower mantle via a resolution analysis. Furthermore, geomagnetic observatories in Northeast Asia were used as case studies. The data misfit in the objective function has been measured using L1-norm. The limited-memory quasi-Newton algorithm is employed to deal with the minimization problem. Earth is discretized by using heterogeneous prisms in a spherical coordinate system with fine grids within the study area. Three-dimensional simulations show that the sparse and internationally shared GDS observatories in East Asia can detect long-wave anomalies larger than 20°. To detect smaller anomalies of ∼6° at depths up to 900 km, a denser spread of GDS observatories is required with a spacing of approximately 200 km. For this denser distribution of observatories, shortening the longest period of C-responses to 42.7 d yields almost the same inversion resolution as that achieved for periods up to 113.8 d in different depths around the Mantle Transition Zone (MTZ). Further testing of broken stagnant plate models confirms the detectability of the stagnating slabs for the denser observatory distribution. Real data inversion revealed a high conductivity anomaly in the MTZ beneath northeastern China, which can be associated with the stagnant slab. Overall, we conclude that the high-resolution electrical conductivity structure in the MTZ can be delineated using dense distributions of GDS observatories. [Display omitted] •Average 200 km station spacing like in the East can delineate anomalies of dimensions 6° by 6°.•Broken slabs in the lower mantle and its remnant portion in the MTZ could be detected.•There is a high-conductivity anomaly in the MTZ of East Asia that could be interpreted as the stagnant Pacific slabs.